2011
DOI: 10.1073/pnas.1100513108
|View full text |Cite
|
Sign up to set email alerts
|

Tsukushi functions as a Wnt signaling inhibitor by competing with Wnt2b for binding to transmembrane protein Frizzled4

Abstract: The Wnt signaling pathway is essential for the development of diverse tissues during embryogenesis. Signal transduction is activated by the binding of Wnt proteins to the type I receptor lowdensity lipoprotein receptor-related protein 5/6 and the seven-pass transmembrane protein Frizzled (Fzd), which contains a Wntbinding site in the form of a cysteine-rich domain. Known extracellular antagonists of the Wnt signaling pathway can be subdivided into two broad classes depending on whether they bind primarily to W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 33 publications
(36 reference statements)
1
65
0
Order By: Relevance
“…In TSK −/− mice, both the ventral and dorsal CB appeared larger than in wild type mice (Ohta et al . ). The canonical Wnt pathway regulates retinal stem cell proliferation (Kubo & Nakagawa ).…”
Section: Neural Stem Nichesmentioning
confidence: 97%
See 2 more Smart Citations
“…In TSK −/− mice, both the ventral and dorsal CB appeared larger than in wild type mice (Ohta et al . ). The canonical Wnt pathway regulates retinal stem cell proliferation (Kubo & Nakagawa ).…”
Section: Neural Stem Nichesmentioning
confidence: 97%
“…These observations indicate that TSK regulates neural stem cells as a niche molecule through its role as a Wnt signaling inhibitor (Ohta et al . , ).…”
Section: Neural Stem Nichesmentioning
confidence: 99%
See 1 more Smart Citation
“…TSK functions as an organizer inducer by inhibiting BMP signaling in cooperation with chordin (Ohta et al, 2004) and interacts with Vg1 to induce the primitive streak and Hensen's node formation in the chick embryo (Ohta et al, 2006). Recently, our group reported that TSK functions as a Wnt signaling inhibitor by competing with Wnt2b for binding to the transmembrane protein Frizzled4 (Ohta et al, 2011). Thus, TSK is a key coordinator of multiple pathways outside the cells through the regulation of an extracellular signaling network (Dellett et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…Overexpression of Wnt2b induces Bmp7 expression and results in thinning of the NR (Ohta et al, 2011), whereas BMP application at ov stages induces Wnt2b and Wnt8b expression Teraoka et al, 2009). By contrast, NR specification requires suppression of Wnt8b in the mouse (Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%